X-ray scaling relations from a complete sample of the richest maxBCG clusters. Issue 2 (10th January 2019) - Ge, Chong; Sun, Ming; Rozo, Eduardo; Sehgal, Neelima; Vikhlinin, Alexey; Forman, William; Jones, Christine; Nagai, Daisuke
ABSTRACT: We use a complete sample of 38 richest maxBCG clusters to study the ICM–galaxy scaling relations and the halo mass selection properties of the maxBCG algorithm, based on X-ray and optical observations. The clusters are selected from the two largest bins of optical richness in the Planck stacking work with the maxBCG richness N 200 ≥ 78. We analyse their Chandra and XMM – Newton data to derive the X-ray properties of the ICM. We then use the distribution of P ( X | N ), X  = TX,   LX,   YX, to study the mass selection P ( M | N ) of maxBCG. Compared with previous works based on the whole richness sample, a significant fraction of blended systems with boosted richness is skewed into this richest sample. Parts of the blended haloes are picked apart by the redMaPPer, an updated red-sequence cluster finding algorithm with lower mass scatter. Moreover, all the optical blended haloes are resolved as individual X-ray haloes, following the established LX − TX and LX − YX relations. We further discuss that the discrepancy between ICM–galaxy scaling relations, especially for future blind stacking, can come from several factors, including miscentring, projection, contamination of low-mass systems, mass bias, and covariance bias. We also evaluate the fractions of relaxed and cool core clusters in our sample. Both are smaller than those from SZ or X-ray selected samples. Moreover, disturbed clusters show a higher level of mass bias than relaxed clusters.